(3GdCQHYjf aj CUhd GdOjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3YKeGf Hf YHO GdQMef Hf GdMSf Hf Ydi s)
(3ChdgG (B:s
(3C(B/(3G HYO aEf Gddg JYGdi deG habfi MJi VaJ ai CcKQ GdYdhe GdOfjfI hgPG GdcJGH OSJhQkG dg HQLY ai GdeVGFb Edjg s
(3BNQgG (B:s
(3hdG jaYd Hi eG CfG Cgdg hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hBdg hCUMGHI CLejYjf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(73) s
Keywords: (3GdJhMjO hGdedd hGdfMds